Optimal placement and active vibration control of composite plates integrated piezoelectric sensor/actuator pairs - Quoc, Tran Huu; Tham, Vu Van; Tu, Tran Minh (Vietnam Journal of Science and Technology, 2018)
In this study, a finite element model based on first-order shear deformation theory is presented for optimal placement and active vibration control of laminated composite plates with bonded distributed piezoelectric sensor/actuator pairs. The model employs the nine-node isoparametric rectangular element with 5 degrees of freedom for the mechanical displacements, and 2 electrical degrees of freedom. Genetic algorithm (GA) is applied to maximize the fundamental natural frequencies of plates; and the constant feedback control method is used for the vibration control analysis of piezoelectric laminated composite plates. The results of this study can be used to aid the placement of piezoelectric sensor/actuator pairs of smart composite plates as well as for robust controller design.